The Impact of Information Technology (IT) on Modern Accounting Systems - Muhammad Fazlan; Zulkarnain Zulkarnain (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to evaluate the impact of Information Technology (IT) on Modern Accounting Systems. The research background reflects a shift in the traditional accounting paradigm towards the increasingly rampant application of information technology. The research method used is literature analysis and case studies. Research findings reveal that IT implementation in modern accounting systems not only increases the efficiency and accuracy of data processing, but also makes a significant contribution to strategic decision making and risk management. The implications of this research include the need to develop IT competencies for accounting professionals, as well as the importance of information security policies in managing financial data. Thus, this research provides insight into the crucial role of IT in the transformation of modern accounting systems and highlights important aspects that need to be considered in facing technological developments in the accounting field.